2016
DOI: 10.3892/mco.2016.883
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 4: A new potential biomarker of lung cancer

Abstract: Lung cancer is most prevalent human cancer worldwide. However, no molecular markers are currently available for predicting lung cancer prognosis. Therefore, identifying novel biomarkers may be useful for improving clinical diagnosis and patient stratification. Krüppel-like factor 4 (KLF4) is a transcription factor with opposing roles in different human cancers. Its overexpression in several cancers is correlated with a poor prognosis. However, the expression and role of KLF4 in lung cancer remains to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 26 publications
4
33
0
2
Order By: Relevance
“…This is the first study showing a significant difference in KLF4 protein and mRNA expression levels between normal and cancerous laryngeal tissues. Our findings were consistent with those reported by different studies showing a tumor suppressor role of KLF4 in several types of cancer, including gastric and colon cancers (6)(7)(8), bladder cancer (35), esophageal cancer (36), and non small cell lung carcinoma (14,37). Of note, in head and neck squamous cell carcinoma malignancies, KLF4 can exert different roles in different types.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is the first study showing a significant difference in KLF4 protein and mRNA expression levels between normal and cancerous laryngeal tissues. Our findings were consistent with those reported by different studies showing a tumor suppressor role of KLF4 in several types of cancer, including gastric and colon cancers (6)(7)(8), bladder cancer (35), esophageal cancer (36), and non small cell lung carcinoma (14,37). Of note, in head and neck squamous cell carcinoma malignancies, KLF4 can exert different roles in different types.…”
Section: Discussionsupporting
confidence: 83%
“…In head and neck squamous cell carcinoma (HNSCC) tissues, persistent KLF4 expression predicts poor prognosis and confers aggressiveness (13). Recent studies showed that KLF4 is upregulated in small cell lung carcinoma tissues and has a potential tumor-promoting role in this type of lung malignancy (14).…”
Section: Introductionmentioning
confidence: 99%
“…Fadous-Khalifé et al (25) demonstrated that, compared with normal tissue, the expression of Kruppel-like factor 4 (KLF4) was markedly decreased in non-small cell lung cancer, although it was overexpressed in small cell lung cancer. In addition, Perini et al (26) demonstrated that the overexpression of membrane epidermal growth factor receptor is associated with decreased survival in pancreas cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the expression of KLF4 is downregulated in the majority of primary lung cancers examined, and ectopic expression of KLF4 suppresses lung cancer cell proliferation and clonogenic formation in vitro , and suppresses tumor growth in vivo (127,128). A recent study showed differential expression of KLF4 in lung cancer, where a significant decrease in KLF4 expression is observed in non-small-cell lung cancer compared with that in normal tissue, while a significant overexpression is detected in small-cell lung cancer (129). …”
Section: Roles In Diseasesmentioning
confidence: 99%